Protective Effect of Resveratrol on Benzo(a)Pyrene Induced Dysfunctions of Steroidogenesis and Steroidogenic Acute Regulatory Gene Expression in Leydig Cells - Banerjee, Bhaswati; Chakraborty, Supriya; Chakraborty, Pratip; Ghosh, Debidas; Jana, Kuladip (Frontiers in Endocrinology, 2019)
Benzo(a)pyrene [B(a)P] is the toxic environmental Polycyclic Aromatic Hydrocarbon (PAH), that exerts male reproductive dysfunctions. In this study the molecular mechanism of B(a)P induced Leydig cell steroidogenic dysfunctions and its protective mechanism of action with a natural Aryl hydrocarbon receptor (AhR) antagonist and anti-oxidant, Resveratrol (Res) has been investigated. B(a)P exposure induced ROS mediated steroidogenic imbalance via activation of p38MAPK and repression of testosterone level as well as other steroidogenic enzymes like CYPIIA1, 3β-HSD, 17β-HSD expressions. B(a)P exposure also decreased StAR protein expression along with increased of DAX-1 protein, a transcriptional repressor of StAR gene expression as well as decreased SF-1 protein also, a transcriptional inducer of StAR gene expression. The study has established that Resveratrol as a potential agent combating the deleterious effect of B(a)P on Leydig cell steroidogenesis. Resveratrol treatment resulted significant protection against B(a)P by scavenging ROS and modulating the transcriptional regulation of anti-oxidant enzymes. Furthermore, Resveratrol also prevented stress kinase like p38 MAPK activation and increased StAR protein expression through the reduction of DAX-1 expression. Moreover, the testosterone production was efficiently restored with Resveratrol treatment. ChIP assay also revealed that resveratrol improved SF-1expression which further increased the StAR gene expression. Resveratrol acted efficiently against B(a)P, through its anti-oxidative properties as well as inhibits p38MAPK and increased steroidogenesis and StAR gene expression through the modulation of SF-1 gene expression.